Association of endoscopic and histological remission with clinical course in patients of ulcerative colitis - Narang, Vikram (Intest Res, 2018)
BACKGROUND/AIMS: The therapeutic goal for treating ulcerative colitis (UC) patients has shifted to achieving mucosal healing over the past few years. However, at present, limited data is available on the correlation between endoscopic findings and histological remission in patients with endoscopic mucosal healing. METHODS: This was a prospective observational study conducted over a period of 18 months (January 2014 to June 2015) at Dayanand Medical College and Hospital, Ludhiana, Punjab, India. Patients diagnosed with UC who had been in clinical remission (n=76) for at least 6 months were evaluated for endoscopic remission. Those in endoscopic remission (Mayo score ≤1; 46/76, 60.5%) were subjected to multiple biopsies from the rectosigmoid region and histological remission, which was then defined as grade 0/1 as per the Geboes criteria. RESULTS: Of the 46 patients in endoscopic remission (age, 18–73 years; male:female=1.5:1.0), majority had E1 (proctitis) disease (21/46, 45.6%) followed by E2 (left sided colitis) (18/46, 39.1%) and E3 disease (pancolitis) (7/46, 15.2%) at baseline. Histological remission was noted in 67.3% (31/46) of the patients, while 32.7% (15/46) still retained the histologically active disease in the form of infiltration of the lamina propria by eosinophils and neutrophils (13/15, 86.6%), cryptitis (14/15, 93.3%), and crypt abscesses (8/15, 53.3%). On follow-up, after 1 year, 87.1% (27/31) of the patients who had been in histological remission remained clinically asymptomatic, while 12.9% (4/31) had relapsed. Among the 15 histologically active patients, 46.6% (7/15) remained in clinical remission, while 53.3% (8/15) had relapsed. CONCLUSIONS: Histological remission, rather than endoscopic remission, predicts a sustained clinical remission and allows monitoring of therapy for the subsequent disease course in patients with UC.